2022
DOI: 10.3390/ani12020174
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Intensification of Beef Production in the Tropics: The Role of Genetically Improving Sexual Precocity of Heifers

Abstract: Increasing productivity through continued animal genetic improvement is a crucial part of implementing sustainable livestock intensification programs. In Zebu cattle, the lack of sexual precocity is one of the main obstacles to improving beef production efficiency. Puberty-related traits are complex, but large-scale data sets from different “omics” have provided information on specific genes and biological processes with major effects on the expression of such traits, which can greatly increase animal genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 162 publications
(268 reference statements)
0
4
0
1
Order By: Relevance
“…In general, puberty traits-particularly the age and weight at first corpus luteum-respond to selection in tropical beef cattle [20]. Genetic characteristics in Zebu cattle that are associated with heifers' puberty and production traits include fat depth, rib fat, body condition, live weight, and Longissimus dorsi muscle area [21]. However, the relationship of growth and fatness with puberty traits is not expected to be linear, which is in agreement with our results that showed that, as measured by progesterone concentration, puberty traits were not achieved naturally at the end of the growing phase.…”
Section: Discussionmentioning
confidence: 99%
“…In general, puberty traits-particularly the age and weight at first corpus luteum-respond to selection in tropical beef cattle [20]. Genetic characteristics in Zebu cattle that are associated with heifers' puberty and production traits include fat depth, rib fat, body condition, live weight, and Longissimus dorsi muscle area [21]. However, the relationship of growth and fatness with puberty traits is not expected to be linear, which is in agreement with our results that showed that, as measured by progesterone concentration, puberty traits were not achieved naturally at the end of the growing phase.…”
Section: Discussionmentioning
confidence: 99%
“…A lucratividade da bovinocultura de corte está associada à redução da idade a maturidade das novilhas, uma vez que permite maior número de bezerros por vaca e maior longevidade produtiva (6)(7)(8)(9) . Novilhas que emprenham no início da estação reprodutiva e parem também no início da estação de nascimento, apresentam bezerros mais pesados e maior tempo de recuperação pós-parto, resultando em maiores chances de se apresentarem prenhas no início das estações reprodutivas subsequentes (10,11) . Assim, a seleção genética para precocidade sexual em novilhas permite otimizar o ciclo produtivo e em sistemas de produção de bovinos de corte a sustentabilidade econômica está relacionada ao crescimento, eficiência reprodutiva, carcaça e produção (12) .…”
Section: Introductionunclassified
“…Beef cattle profitability is associated with reduced onset of females' maturity since it allows for a greater number of calves to be produced per cow and increased productive longevity (6)(7)(8)(9) . Heifers that calve earlier during the calving season have heavier calves and a longer post-partum recovery time, resulting in increased chances of displaying early pregnancies in subsequent breeding seasons (10,11) . Thus, the genetic improvement of heifers' sexual precocity allows optimizing the productive cycle, and, in a beef cattle production system, economic sustainability is related to growth, reproductive efficiency, carcass, and production (12) .…”
Section: Introductionmentioning
confidence: 99%